Parametric Study Of Geodesic Dome Subjected To Wind Load For Different Geodesic Frequencies - Jitender Kumar; Deepak Bahuguna; Abhishek Singh; Suresh Kumar choudhary; Dr. Ayub Shaikh (Revista Electronica de Veterinaria, 2024)
Domes have been a prominent part of construction dating back from ancient times due to its uniqueness in providing maximum space with minimum surface area. Their popularity lost ground during the medieval period on account of tedious construction methods and skilled work requirements for large sized domes. The paper brings out the various advantages and key aspects of geodesic domes as the modern world looks out for energy efficient, eco-friendly and durable housing options. In this paper, comparison of geodesic dome is carried out for 60 meter diameter and class 1 division method. Class1 method1 is used for different frequencies like 5V, 10V, 15V, 20V, 25V. Model of dome is generated in CADRE GEO 7.0 software. Analysis and design is carried out by STAAD Pro V8i SS5. Optimization is performed using STAAD in-built optimization tool.In order to study the behavior of geodesic dome ratio of height to diameter of dome kept same as 0.5. This paper takes a look into the combination of impact of wind load for different zones with different geodesic frequencies. In this paper, the performance of anti-seism of a large-scale geodesic dome is studied with time history method.